Productive Zakat in Yusuf Qardha Community Economic Empowerment Through Productive Zakat in Yusuf Qardhawi's Fiqh Perspective - Adib, Roisul (Iqtishodia: Jurnal Ekonomi Syariah, 2022)
Zakat in Islam is the right of the poor that is found in some of the assets of people who are obliged to pay zakat. And zakat also in the era of the glory of Islam has proven to play a very important role in improving the welfare of the people and zakat is made as a responsibility for Muslims to help each other. Yusuf Qardhawi defines zakat as part of the wealth that has been determined by Allah SWT to be distributed to people who deserve to get it. The form of zakat in the form of money is categorized into two types, namely consumptive zakat and productive zakat, where the majority of Muslims mostly know about consumptive zakat and do not know about productive zakat which can last in the long term. From this background, the authors formulate the problems, among others: the view of productive zakat according to Fiqh Yusuf Qardhawi and community economic empowerment through productive zakat. As for getting maximum results, the type of research used is normative research, while the qualitative approach is in the form of a literature study which is intended to describe current or past phenomena and also to compare different opinions about the problems being studied. As a result, according to Yusuf Qardhawi, Zakat is a Maliyah Ijtimaiyah worship which can be interpreted as a social worship related to the benefit of the people. Yusuf Qardhawi gives two points, first, the role of zakat in overcoming economic problems in society and second, the management of zakat which can support success in zakat.